Laparoscopic treatment of congenital portosystemic shunts with portal pressure measurement and portal angiography in 36 dogs - Shigemoto, Jin; Kaneko, Yasuyuki; Kawazu, Mitsunobu; Naganobu, Kiyokazu; Torisu, Shidow (Frontiers in Veterinary Science, 2024)
Introduction: Laparoscopic surgery is used for canine congenital extrahepatic portosystemic shunts (CEHPSS). However, outcomes of laparoscopic surgery involving simultaneous portal vein angiography and portal pressure measurement to attenuate or completely occlude the shunt vessel in canines remain unclear. This study aimed to evaluate outcomes and complications of laparoscopic portosystemic shunt occlusion (LAPSSO) for CEHPSS. Methods: Between June 2014 and March 2021, data on dogs undergoing cellophane banding (CB) and complete occlusion of laparoscopically treated congenital extrahepatic port shunts were collected from hospital records. Cases in which complete occlusion was laparoscopically performed, or a CB was used for gradual occlusion were included. A total of 36 dogs (14 males; median age 32.5 months [range, 5-99] with median body weight, 4.2 kg [range, 1.5-7.9]) that underwent LAPSSO for CEHPSS were included. All the dogs underwent computed tomographic angiography (CTA), and data on blood and radiological examinations were collected. Shunt vessel morphology was categorized using CTA findings. Portal pressure measurements and portal angiography were performed by accessing mesenteric and splenic veins in 30 and 6 cases, respectively. Results: The most common shunt types were spleno-phrenic shunts 16/36 (44.4%), followed by spleno-azygos 9/36 (25.0%), spleno-caval 4/36 (11.1%), right gastric-caval 6/36 (16.6%), and right gastric-caval with caudal loop shunts 1/36 (2.7%). The median portal pressure after complete occlusion was 11.5 mmHg (range, 4-16); portal pressures in the two dogs undergoing CB attenuation were 22 and 24 mmHg. The median operating time in the dogs with right (n=25) and left (n=11) recumbent positioning was 55 min (range, 28-120) and 54 min (range, 28-88), respectively. One dog had pneumothorax due to injury to the diaphragm. Another dog developed postoperative hypernatremia and succumbed 5 hours post-procedure. Nevertheless, no other dogs exhibited signs of portal hypertension within 72 hours. Blood tests and abdominal ultrasounds performed 1-2 months postoperatively revealed no residual shunts. Discussion: LAPSSO, coupled with portal pressure measurement and portal angiography, was shown as safe and effective approach that facilitated successful occlusion of CEHPSS. Further large-scale prospective studies and analyses of perioperative complications are needed.